2000
DOI: 10.1136/tc.9.suppl_3.iii78
|View full text |Cite
|
Sign up to set email alerts
|

Quit for keeps: tailored smoking cessation guides for pregnancy and beyond

Abstract: Although health care providers appear to be an obvious choice for delivering smoking cessation education, they often lack the resources, training, and time to provide anything more than a recommendation to quit and generic pamphlets for reinforcement. Traditionally, this type of material is designed to include information for many potential users, thus making it diYcult for an individual to find the pieces most relevant to them. In contrast, tailored print materials provide only information which is relevant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…38 The participating clinics serve women from a range of socioeconomic backgrounds including many with Medicaid. Site 1 included an obstetric and gynecology (OB-GYN) clinic in Michigan, and Site 2 included 2 adjoining OB-GYN clinics in North Carolina.…”
Section: Participantsmentioning
confidence: 99%
“…38 The participating clinics serve women from a range of socioeconomic backgrounds including many with Medicaid. Site 1 included an obstetric and gynecology (OB-GYN) clinic in Michigan, and Site 2 included 2 adjoining OB-GYN clinics in North Carolina.…”
Section: Participantsmentioning
confidence: 99%
“…Recruiting participants for clinical trials can be challenging in general (e.g., Harris et al, 2003;Ross et al, 1999), and this has been particularly the case for smoking cessation trials of pregnant women, which often have difficulty meeting accrual goals (e.g., Cinciripini et al, 2000;Emmons et al, 2000;Goldenberg et al, 2000; Pollak et al, 2006;Ruggiero et al, 2003;Solomon et al, 2000;Strecher et al, 2000). Trials focusing on relapse prevention with this population have the additional challenge of recruiting from a yet smaller proportion of the population: pregnant women who smoked prior to their pregnancy but are currently abstaining from smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, by resuming smoking, the mother also reexposes herself to the myriad health risks associated with tobacco use. Given the high rate of self-quitting among pregnant smokers, as well as the success of interventions designed to motivate pregnant women to quit smoking (Melvin et al, 2000), pregnancy and the early postpartum period appear to offer unique opportunities to provide smoking relapseprevention interventions, although such efforts have met with at best modest success to date (Mullen, 2004).Recruiting participants for clinical trials can be challenging in general (e.g., Harris et al, 2003;Ross et al, 1999), and this has been particularly the case for smoking cessation trials of pregnant women, which often have difficulty meeting accrual goals (e.g., Cinciripini et al, 2000;Emmons et al, 2000;Goldenberg et al, 2000; Pollak et al, 2006;Ruggiero et al, 2003;Solomon et al, 2000;Strecher et al, 2000). Trials focusing on relapse prevention with this population have the additional challenge of recruiting from a yet smaller proportion of the population: pregnant women who smoked prior to their pregnancy but are currently abstaining from smoking.…”
mentioning
confidence: 99%
“…Sensitivity analyses were carried out excluding trials that recruited pregnant quitters at baseline, and did not separate them from smokers for analysis [21,24], that provided more than 15 minutes of contact time [20], and included either clinical reinforcement or where it was difficult to determine whether face‐to‐face contact included any smoking cessation counselling [25–27]. These ‘borderline trials’ were removed from analyses in order to establish whether they introduced bias [28].…”
Section: Methodsmentioning
confidence: 99%
“…The remaining three trials of the 15 identified compared a self‐help booklet to tailored self‐help guides [24], basic self‐help materials to the same materials plus six self‐help videos [29] and a self‐help booklet to the same booklet plus a tailored interactive telephone system [37]. Two of these trials provided the more intensive experimental arm materials by post [24,29]; the other provided an information brochure about the telephone system by post and a 10‐minute phone call instructing participants on its use [37].…”
Section: Methodsmentioning
confidence: 99%